Comparison Of Middle Ear Soft Tissue Density Of Chronic Otitis Media With Cholesteatoma By CT - Tok, Sermin; Altınkaya, Naime; Ozer, Fulya (ENT Updates, 2018)
Objective: Chronic otitis media is the infection of the middle ear and mastoid air cells. Cholesteatoma is keratinized squamous epithelium formation in the middle ear. Although the two diseases may be recognized with clinical examination, sometimes it may not be possible. While treatment of chronic otitis media includes antibiotic therapy or surgery, cholesteatoma is treated surgically. In this study, we aimed whether quantitative measurement of the soft tissue density in the middle ear on temporal bone CT may be used as a criterion for discrimination of chronic otitis media and cholesteatoma. Materials and Methods: A total of 45 patients were included in the study. Multi-slice CT images were obtained in supine position for temporal bone CT. The soft tissue density was measured using free hand and circle region of interest (ROI) techniques on temporal bone CT examinations. Results: A statistically significant difference was not detected between cholesteatoma and COM with regard to HU values on temporal bone CT in ROC curve. P value and Mann Whitney U was not statistically significant. Conclusion: As a result, soft tissue density measurement is not statistically significant for differential diagnosis of COM and cholesteatoma.